Bencana Banjir: Pengawasan dan Pengendalian Pemanfaatan Ruang Berdasarkan UU Penataan Ruang dan RUU Cipta Kerja - Qodriyatun, Sri Nurhayati (Jurnal Aspirasi, 2020)
Floods almost occurred in most parts of Indonesia, including in Bengkulu. The cause of floods in Bengkulu is more due to human behavior factors, namely massive land conversion. Even though the Spatial Planning Law already regulates how the use of space should be done and how to control it. On the other hand, the government is currently planning to change the rules regarding spatial planning to facilitate licensing in investment through the Job Creation Bill. In the bill, the authority of spatial planning is the authority of the central government. The problem is how the supervision and control of spatial use are carried out in Bengkulu and what about the supervision of spatial use control later if the spatial planning authority is centralized in the central government? By using a literature study, the study shows that the central government and the regional government of Bengkulu have not conducted supervision and control over spatial use as stipulated in the Spatial Planning Law. It was proven that it only conducted a review of Bengkulu Province Spatial Planning without conducting law enforcement for violations of spatial use. On the other hand, the spatial audit conducted by the Ministry of Agrarian Affairs and Spatial Planning was not running as it should. If the authority of spatial planning is centralized to the central government, as stated in the Job Creation Bill, it is feared that the misuse of spatial use in the regions will increase. Likewise, the occurrence of the flood as a result of increased environmental damage due to spatial use that is not following its designation and function. Therefore, it is necessary to review again the plan to revoke the authority of spatial planning at the regency/city level and the provincial government level in the Job Creation Bill.AbstrakBanjir hampir terjadi di sebagian besar wilayah Indonesia, termasuk di Bengkulu. Penyebab banjir di Bengkulu lebih dikarenakan faktor perilaku manusia, yaitu alih fungsi lahan yang masif. Padahal Undang-Undang tentang Penataan Ruang (UU Penataan Ruang) sudah mengatur bagaimana pemanfaatan ruang seharusnya dilakukan dan bagaimana pengendaliannya. Di sisi lain, saat ini pemerintah berencana akan mengubah aturan mengenai penataan ruang ini untuk mempermudah perizinan dalam investasi melalui RUU tentang Cipta Kerja. RUU mengatur kewenangan penataan ruang merupakan kewenangan pemerintah pusat. Permasalahannya adalah bagaimana pengawasan dan pengendalian pemanfaatan ruang dilakukan di Bengkulu dan bagaimana dengan pengawasan pengendalian pemanfaatan ruang nantinya jika kewenangan penataan ruang dipusatkan di pemerintah pusat? Studi literatur digunakan untuk mengkaji dan hasil kajian menunjukkan bahwa pemerintah pusat maupun Pemerintah Daerah Provinsi Bengkulu belum melakukan pengawasan dan pengendalian pemanfaatan ruang sebagaimana yang diatur dalam UU Penataan Ruang. Terbukti hanya melakukan review RTRW Provinsi Bengkulu tanpa melakukan penegakan hukum atas pelanggaran pemanfaatan ruang. Di sisi lain, audit tata ruang yang dilakukan Kementerian ATR/BPN tidak berjalan sebagaimana mestinya. Jika kewenangan penataan ruang dipusatkan ke pemerintah pusat, sebagaimana disebutkan dalam RUU Cipta Kerja, dikhawatirkan penyalahgunaan pemanfaatan ruang di daerah semakin meningkat. Demikian juga dengan kejadian banjir sebagai dampak dari meningkatnya kerusakan lingkungan akibat pemanfaatan ruang yang tidak sesuai peruntukan dan fungsinya. Oleh karena itu, perlu kiranya ditinjau kembali mengenai rencana mencabut kewenangan penataan ruang di tingkat kabupaten/ kota dan di tingkat pemerintah provinsi dalam RUU Cipta Kerja.